Análisis de la contaminación por microplásticos en los ríos Malacatos y Zamora de la ciudad de Loja - Romero Lopez, Angel Israel (2025)
Microplastics pose a serious threat to both marine and terrestrial biota, as they negatively impact the quality of soil, water and air. In Ecuador, various bodies of water have been reported to exhibit significant accumulation of plastic waste, including the presence of microplastics. Specially, in the city of Loja, various types of waste are discarded along the Malacatos and Zamora rivers. Potentially altering the ecological characteristics of these habitats. In response to this 4 environmental concern, the present study evaluated the level of water contamination by microplastics at three sampling points along the confluence of these rivers. The methodology consisted on three phases: assessment of microplastic concentration, determination of water quality, and evaluation of toxicity using the Artemia salina bioassay. The results confirmed the presence of microplastic in the study area based on their morphological characteristics. However, some limitations were encountered in completely separating the microplastics from the sediments for further analysis. Additionally, the sediments were found to contribute to moderate water quality levels and presented a high ecotoxicological risk to Artemia salina (90% to 97% mortality), with microplastics in the sediments estimated to be a major contributing factor due to their intrinsic toxicity (70% to 75%). Overall, the analyses suggested that microplastics constitute a considerable source of contamination in both rivers, as they are integrated into the sediments’ composition, which in turn significantly impacted water quality and ecotoxicological risk. There findings underscore the urgent need to implement control measures to reduce waste accumulation in these rivers and preserve the health of these ecosystems.